Rapidly-formable high-wear-resistant coating for industrial conveyor belt and preparation method thereof

By using a high wear-resistant coating composed of component A composed of diisocyanate and polyether polyol and component B composed of component A and terminal amino polyethers on industrial conveyor belts, the problem of poor wear resistance of the conveyor belt under harsh working conditions is solved, rapid molding and efficient protection of the coating are achieved, extending the service life of the conveyor belt and reducing production costs.

CN119842308APending Publication Date: 2025-04-18XIAN UNIV OF TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510078053.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing industrial conveyor belt coating has poor wear resistance under harsh working conditions, complex preparation process and difficult to achieve large-scale industrial production.

Method used

A high wear-resistant coating consisting of components A and components B, which consists of diisocyanate and polyether polyols, and component B consists of end amino polyethers, chain extenders, wear-resistant fillers and additives, and is rapidly formed through the spraying process.

Benefits of technology

It significantly improves the impact resistance and toughness of industrial conveyor belts, extends the service life of the conveyor belt, reduces replacement frequency and downtime, and complies with the environmental and safety requirements of modern industry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119842308A_ABST
    Figure CN119842308A_ABST
Patent Text Reader

Abstract

The invention discloses a high-wear-resistance coating capable of being rapidly formed for an industrial conveyor belt and a preparation method thereof.The high-wear-resistance coating comprises a component A and a component B. The component A is composed of diisocyanate and polyether polyol, and in percentage by weight, the component A comprises 13-21% of free isocyanato, 20-30% of polyether polyol and the balance of water. The component B is composed of amino-terminated polyether, a chain extender, a wear-resistant filler and an auxiliary agent, and the wear-resistant filler is modified halloysite nanotubes (HNTs); and the isocyanate index of the component A and the component B is 1.05-1.1. The high-wear-resistant coating capable of being quickly formed for the industrial conveyor belt has a good protection effect on the conveyor belt, can effectively resist friction, scraping and impact effects of materials when the conveyor belt is in contact with the conveyed materials, ensures the basic mechanical properties of the coating, remarkably improves the wear resistance and aging resistance of the coating, and has a good application prospect. And the requirement of long-term stable operation of the industrial conveyor belt under severe working conditions is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wear-resistant materials, and relates to a high wear-resistant coating that can be quickly formed for industrial conveyor belts. The invention also relates to a preparation method of the high wear-resistant coating. Background Art

[0002] In the context of the rapid development of automated factories, industrial conveyor belts, as a key automation equipment, are becoming increasingly important. However, in actual applications, industrial conveyor belts often face harsh working environments, such as high loads, high speeds, and complex working conditions. These factors make the surface of industrial conveyor belts susceptible to wear, corrosion, and other damage, seriously affecting their service life and transmission efficiency. Therefore, improving the wear resistance of the conveyor belt surface and extending its service life have become urgent issues to be solved.

[0003] In recent years, a variety of optimization measures have been taken to address the above problems, such as optimizing the design of feeding devices, reducing material impact, and using repair agents for local repairs. Although these methods have worked to a certain extent, they still cannot meet the increasingly stringent requirements of modern industry in terms of wear resistance, impact resistance, and aging resistance. Compared with other protective materials, polymer wear-resistant coatings have high hardness and excellent wear resistance, which can effectively reduce friction damage, extend the service life of equipment, and improve production efficiency.

[0004] The invention patent with publication number CN103951278B provides a nano coating with high wear resistance, high weather resistance, super hydrophobicity and super oleophobicity and its preparation method, which can maintain good performance under high-intensity friction or harsh environment, but its preparation process is relatively complicated and difficult to achieve large-scale industrial production. The invention with publication number CN110318036B discloses a titanium carbide wear-resistant ceramic coating and its preparation method, but this method requires high temperature above 1000°C for deposition, which is still unbearable for general substrates.

[0005] In summary, although the existing coating technology has made some progress in improving the wear resistance and service life of industrial conveyor belts, there are still problems such as insufficient wear resistance, complex preparation process and application limitations. How to achieve a simpler preparation method while maintaining the high performance of the coating and adapt to a wider range of industrial applications is still a key technical problem that needs to be solved urgently. Summary of the invention

[0006] The purpose of the present invention is to provide a high wear-resistant coating that can be quickly formed for industrial conveyor belts, thereby solving the problem of poor wear resistance of industrial conveyor belts under harsh working conditions in the prior art.

[0007] Another object of the present invention is to provide a method for preparing the above-mentioned high wear-resistant coating that can be quickly formed for industrial conveyor belts.

[0008] The technical solution adopted by the present invention is a high wear-resistant coating that can be quickly formed for industrial conveyor belts, including component A and component B. Component A is composed of diisocyanate and polyether polyol by weight, and the free isocyanate content in component A is 13% to 21% by weight; component B is composed of 45% to 60% of amino-terminated polyether, 35% to 50% of chain extender, 1% to 3% of wear-resistant filler and 1% to 5% of auxiliary agent by weight; the isocyanate index of component A and component B is 1.05 to 1.1.

[0009] The present invention is also characterized in that:

[0010] Calculated by weight percentage, the diisocyanate in component A accounts for 45% to 70% and the polyether polyol accounts for 30% to 55%.

[0011] The diisocyanate is any one or more of MDI, IPDI and TDI in any proportion.

[0012] The polyether polyol is any one of PPG2000 and PTMG1000 or a combination of the two in any proportion.

[0013] The amino-terminated polyether is any one or more of D400, D2000 and T5000 in any proportion.

[0014] The chain extender is any one or more of E100, E230, W6200, propylene glycol diethyl ester (PGDA), 4,4'-di-sec-butylaminodiphenylmethane (MDBA), BYK-P-104, BYK-104S, dibutyl phthalate (DBP), dioctyl phthalate (DOP), propyl carbonate (PC), and ethyl carbonate (EC) in any proportion.

[0015] The auxiliary agent is any one or more of dibutyl phthalate (DBP), dioctyl phthalate (DOP), propyl carbonate (PC), ethyl carbonate (EC), -P-104, BYK-104S, and dimethyl methylphosphonate (DMMP) in any proportion.

[0016] The wear-resistant filler is modified halloysite nanotubes.

[0017] The second technical solution adopted by the present invention is that the preparation method of the above-mentioned high wear-resistant coating capable of rapid prototyping for industrial conveyor belts is specifically implemented according to the following steps:

[0018] S1. Preparation of component A: diisocyanate was added to a glass reactor, and polyether polyol was slowly added through a constant pressure dropping funnel under a nitrogen atmosphere until the free isocyanate content was 13% to 21%, and then heated in a water bath to 50 to 80° C., kept warm and stirred for 2 to 6 hours to obtain component A;

[0019] S2, preparing component B: according to the isocyanate index of component A and component B of 1.05 to 1.1, determine the weight percentage of each component in component B, first take the amino-terminated polyether, chain extender and auxiliary agent and stir and mix them in the temperature range of 50 to 80° C., then add the wear-resistant filler and continue stirring for 1 to 3 hours until fully mixed to obtain component B;

[0020] S3. Load component A and component B with a volume ratio of 1:1 into the barrel of the spray equipment respectively; set the spraying pressure of the spray equipment to 12-14 MPa, the temperature to 70-75°C, and the output to be not less than 1.6 kg / min; maintain a distance of 35-50 cm between the nozzle and the surface to be sprayed for spraying.

[0021] The second technical solution of the present invention is also characterized in that:

[0022] The wear-resistant filler in S2 is modified halloysite nanotubes, and the specific steps of its preparation method are:

[0023] S2-1, surface treatment: the halloysite nanotubes are dispersed and immersed in a dilute hydrochloric acid solution with a pH value of 2 to 3, and ultrasonically treated at a temperature of 20 to 25°C with a frequency of 20 to 50 kHz for 20 to 40 minutes, and then stirred at room temperature for 1 to 4 hours to obtain a suspension, and then the suspension is separated, and the separated nanotubes are washed with deionized water until neutral, and then dried in a vacuum drying oven at 50 to 80°C for 12 to 24 hours;

[0024] S2-2, modification treatment: grinding the surface-treated halloysite nanotubes into a powder with a particle size of 50-100 nm, adding it to a silane coupling agent solvent with a concentration of 2-4 vol.%, and ultrasonically dispersing it at a temperature of 20-25° C. and a frequency of 20-50 kHz for 30-60 min; wherein the silane coupling agent of the silane coupling agent solution is kH550 or kH570, and the solvent is anhydrous ethanol;

[0025] S2-3, post-treatment: heating in a water bath at 50-70°C with stirring for 2-4 hours to obtain a suspension; washing with water, washing with alcohol, centrifuging, and drying in a vacuum drying oven at 50-80°C for 12-24 hours to obtain completely dried modified halloysite nanotubes.

[0026] The beneficial effects of the present invention are:

[0027] The high wear-resistant coating for industrial conveyor belts that can be quickly formed of the present invention is usually used for industrial conveyor belts, has greatly improved impact resistance and toughness, and has excellent wear resistance. It plays a good protective role on the conveyor belts. When the conveyor belt is in contact with the conveyed material, it can effectively resist the friction, scratching and impact of the material, greatly slowing down the speed of wear on the surface of the conveyor belt, avoiding problems such as breakage and thinning of the conveyor belt due to excessive wear, thereby significantly extending the overall service life and reducing the cost and downtime caused by frequent replacement of conveyor belts; and the spraying operation is convenient, time-saving and labor-saving, and the requirements for equipment and operating environment are not high; its composition and preparation process meet the requirements of modern industry for environmental protection and safety. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a record of the impact force of the high wear-resistant coating that can be quickly formed for industrial conveyor belts of the present invention in the impact resistance test;

[0029] Figure 2 It is a stress-strain curve diagram of the high wear-resistant coating capable of rapid prototyping for industrial conveyor belts of the present invention. DETAILED DESCRIPTION

[0030] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0031] The invention discloses a high wear-resistant coating capable of rapid prototyping for industrial conveyor belts, comprising component A and component B, wherein component A is composed of diisocyanate and polyether polyol, and the free isocyanate content in component A is 13% to 21% by weight; and component B is composed of 45% to 60% of amino-terminated polyether, 35% to 50% of chain extender, 1% to 3% of wear-resistant filler and 1% to 5% of auxiliary agent by weight.

[0032] The isocyanate index of component A and component B (the ratio of the amount of isocyanate equivalent particles in component A of the semi-prepolymer to the amount of terminal amino polyether and chain extender equivalent substances in component B during compounding) is 1.05 to 1.1.

[0033] Calculated by weight percentage, component A contains 45% to 70% of diisocyanate and 30% to 55% of polyether polyol.

[0034] The diisocyanate is any one or more of diphenylmethane diisocyanate (MDI), isophorone diisocyanate (IPDI) and toluene diisocyanate (TDI) in any proportion.

[0035] The polyether polyol is any one of polypropylene glycol 2000 (PPG2000) and polytetramethylene glycol 1000 (PTMG1000) or a combination of the two in any proportion.

[0036] The amino-terminated polyether is any one or more of D400, D2000 and T5000 in any proportion.

[0037] The chain extender is any one or more of E100, E230, W6200, propylene glycol diethyl ester (PGDA), 4,4'-di-sec-butylaminodiphenylmethane (MDBA), BYK-P-104, BYK-104S, dibutyl phthalate (DBP), dioctyl phthalate (DOP), propyl carbonate (PC), and ethyl carbonate (EC) in any proportion.

[0038] The auxiliary agent is any one or more of dibutyl phthalate (DBP), dioctyl phthalate (DOP), propyl carbonate (PC), ethyl carbonate (EC), -P-104, BYK-104S, and dimethyl methylphosphonate (DMMP).

[0039] The wear-resistant filler is modified halloysite nanotubes.

[0040] By adjusting the formula of component A, the strength and hardness of the material are improved.

[0041] Diisocyanate is highly reactive, and its typical chemical reaction is a gradual polymerization reaction with polyols to form polyurethane. In wear-resistant coatings, polyurethane is used as a matrix material to provide a basic structural framework for the entire coating, giving it a certain degree of flexibility, strength, and adhesion, so that it can better fit the surface of the coated object, and also lays the foundation for the subsequent addition of other ingredients such as wear-resistant fillers.

[0042] In addition to reacting with polyols, diisocyanates can also react with themselves or other compounds containing active groups to further form a cross-linked network structure. The cross-linked structure helps to increase the hardness of the coating, making the coating more capable of resisting friction and wear of the material, and can also enhance the chemical resistance of the coating.

[0043] The flexibility of the coating can be flexibly adjusted by changing the ratio of raw materials such as diisocyanate and polyol, selecting polyols with different structures, and choosing different types of diisocyanates.

[0044] By adjusting the B component formula, the molecular chain length is increased and the cross-linking density is improved.

[0045] Increasing the weight percentage of short-chain E100 and MDBA, while shortening the weight percentage of long-chain D2000 and T5000, allows the long and short chains to react alternately to form an interlocking network structure, thereby increasing the crosslinking density.

[0046] Wear-resistant fillers are introduced into the coating, and after chemical modification, they form a strong bond with the polyurea matrix through hydrogen bonds, van der Waals forces or covalent bonds. This bond fills the gaps in the coating and plays a "pinning" role, hindering the movement of molecular chains, greatly improving the hardness and wear resistance of the coating.

[0047] The coordinated adjustment of components A and B achieves a balance between coating strength and toughness, and improves the performance of the coating under impact loads.

[0048] Based on the requirements of spraying technology, designing component A into a semi-prepolymer can reduce the spraying viscosity, make the physical and chemical properties of the cured product more stable, and have moderate activity in the reaction; if the free isocyanate content is too low, the viscosity of the synthetic material will be high, which is not conducive to mixing; if the free isocyanate content is too high, although the viscosity decreases, the reaction speed is too fast, the reaction is difficult to control, the internal stress of the coating is large, and it has a negative effect on adhesion and appearance. Therefore, in the design of the proportion of component A, the semi-prepolymer content is required to be between 13% and 21%.

[0049] The isocyanate index refers to the ratio of the amount of isocyanate equivalent particle material in the semi-prepolymer to the amount of the equivalent material of the interrupter and polyether and chain extender in component B during compounding, and is set between 1.05 and 1.1.

[0050] When it is lower than 1.05, the performance of the obtained coating varies greatly and is not stable; when it is higher than 1.1, the isocyanate groups are excessive, and the excess isocyanate groups will react with moisture in the air, causing the coating to blister and crack, etc. Therefore, when the free isocyanate content in component A is determined during the batching process, a coating with a certain strength and toughness can be prepared according to the isocyanate index of 1.05 to 1.1.

[0051] The present invention also provides a method for preparing the above-mentioned high wear-resistant coating capable of rapid prototyping for industrial conveyor belts, comprising the following steps:

[0052] S1. Preparation of component A: diisocyanate was added to a glass reactor, and polyether polyol was slowly added through a constant pressure dropping funnel under a nitrogen atmosphere until the free isocyanate content was 13% to 21%, and then heated in a water bath to 50 to 80° C., kept warm and stirred for 2 to 6 hours to obtain component A;

[0053] S2, preparing component B: according to the isocyanate index of component A and component B of 1.05 to 1.1, determine the weight percentage of each component in component B, first take the amino-terminated polyether, chain extender and auxiliary agent and stir them evenly in the temperature range of 50 to 80° C., then add the wear-resistant filler and continue stirring for 1 to 3 hours until the mixture is evenly mixed to obtain component B;

[0054] S3. Load component A and component B with a volume ratio of 1:1 into the barrel of the spray equipment respectively; set the spraying pressure of the spray equipment to 12-14 MPa, the temperature to 70-75°C, and the output to be not less than 1.6 kg / min; maintain a distance of 35-50 cm between the nozzle and the surface to be sprayed for spraying.

[0055] The wear-resistant filler in S2 is a modified halloysite nanotube, which is obtained by mixing and modifying halloysite nanotubes (HNTs) and a silane coupling agent. The specific steps of the preparation method of the modified halloysite nanotube are as follows:

[0056] S2-1, surface treatment: disperse and immerse the halloysite nanotubes in a dilute hydrochloric acid solution with a pH value of 2 to 3, use ultrasound at a frequency of 20 to 50 kHz for 20 to 40 minutes at a temperature of 20 to 25°C, and then stir at room temperature for 1 to 4 hours to obtain a suspension, and then separate the suspension, wash the separated nanotubes with deionized water until neutral, and then dry them in a vacuum drying oven at 50 to 80°C for 12 to 24 hours;

[0057] S2-2, modification treatment: grind the surface-treated halloysite nanotubes into powder with a particle size of 50-100 nm, add them into a silane coupling agent solution, and perform ultrasonic dispersion at a temperature of 20-25° C. and a frequency of 20-50 kHz for 30-60 min; the concentration of the silane coupling agent solution is 2-4 vol.%, the silane coupling agent is kH550 or kH570, and the solvent is anhydrous ethanol;

[0058] S2-3, post-treatment: heating in a water bath at 50-70°C with stirring for 2-4 hours to obtain a suspension; washing with water, washing with alcohol, centrifuging, and drying in a vacuum drying oven at 50-80°C for 12-24 hours to obtain completely dried modified halloysite nanotubes.

[0059] The high wear-resistant coating provided by the present invention can be quickly prepared by a spraying process, and can be reacted and formed on the surface of an industrial conveyor belt within three minutes without additional heating, and can be put into practical use within ten minutes, greatly improving construction efficiency and shortening downtime. After the wear-resistant coating is cured and cured at room temperature for seven days in the dark, it can be tested.

[0060] The high wear-resistant coating used in the present invention does not contain harmful chemicals and volatile organic compounds, and meets the requirements of modern industry for environmental protection and safety. The preparation process of the coating does not generate pollution and has good environmental performance.

[0061] Example 1

[0062] In this embodiment, the highly wear-resistant coating that can be quickly formed for industrial conveyor belts includes component A and component B. Component A is composed of diisocyanate and polyether polyol, and the free isocyanate content in component A is 13% by weight; component B is composed of 45% to 60% of amino-terminated polyether, 35% to 50% of chain extender, 1% to 3% of wear-resistant filler and 1% to 5% of additives by weight; wherein the wear-resistant filler is modified halloysite nanotubes.

[0063] The method for preparing the above-mentioned high wear-resistant coating capable of rapid prototyping for industrial conveyor belts in this embodiment comprises the following steps:

[0064] S1. Preparation of component A: Add 200.9 g of MDI-50 and 250 g of PPG-2000 into a glass reactor, keep warm at 50° C. and stir for 2 h under a nitrogen atmosphere to obtain a semi-prepolymer component A having a free isocyanate content of 13%;

[0065] S2. Prepare component B: according to the isocyanate index of component A and component B of 1.1, add 32 g of T5000, 250 g of D2000, 70 g of E100 and 65 g of MDBA into a beaker, stir magnetically at 50° C. until mixed evenly, and finally add 1.3 g of modified halloysite nanotubes and stir and mix evenly to obtain component B;

[0066] S3. Load component A and component B with a volume ratio of 1:1 into the two barrels of the spraying equipment respectively, set the spraying pressure of the spraying equipment to 12MPa, the temperature to 70°C, the output to not less than 1.6kg / min, and keep the nozzle 35cm away from the surface to be sprayed.

[0067] The specific steps of the preparation method of modified halloysite nanotubes in S2 are:

[0068] S2-1, surface treatment: 2g of halloysite nanotubes were dispersed and immersed in 200ml of 0.1mol dilute hydrochloric acid solution, and ultrasonicated at 20-50kHz for 20min at 25°C, and then stirred at room temperature for 1h to obtain a suspension, and then the suspension was separated, and the separated nanotubes were washed with deionized water until neutral, and then dried in a vacuum drying oven at 50°C for 12h;

[0069] S2-2, modification treatment: grind the surface-treated halloysite nanotubes into powder with a particle size of 50-100 nm, add them into 100 ml of silane coupling agent solution with a concentration of 3.5 vol.%, and perform ultrasonic dispersion at a temperature of 25° C. and a frequency of 20-50 kHz for 30-60 min; wherein the silane coupling agent of the silane coupling agent solution is kH550, and the solvent is anhydrous ethanol;

[0070] S2-3. Post-treatment: heating and stirring in a water bath at 50° C. for 3 h to obtain a suspension, washing with water, washing with alcohol, and centrifuging, and drying in a vacuum drying oven at 50-80° C. for 12 h to obtain modified halloysite nanotubes.

[0071] Example 2

[0072] In this embodiment, the highly wear-resistant coating that can be quickly formed for industrial conveyor belts includes component A and component B. Component A is composed of diisocyanate and polyether polyol, and the free isocyanate content in component A is 15% by weight; component B is composed of 45% to 60% of amino-terminated polyether, 35% to 50% of chain extender, 1% to 3% of wear-resistant filler and 1% to 5% of additives by weight; wherein the wear-resistant filler is modified halloysite nanotubes.

[0073] The method for preparing the high wear-resistant coating for the industrial conveyor belt in this embodiment includes the following steps:

[0074] S1. Preparation of component A: 204.7 g of MDI-50 and 200 g of PPG-2000 were added to a glass reactor, and the mixture was kept warm in a water bath at 80° C. under a nitrogen atmosphere and stirred for 6 h to obtain a semi-prepolymer component A having a free isocyanate content of 15%;

[0075] S2. Prepare component B: according to the isocyanate index of component A and component B of 1.05, add 20 g of T5000, 230 g of D2000, 80 g of E100 and 74 g of MDBA into a beaker, stir magnetically at 80° C. until mixed evenly, and finally add 2.6 g of modified halloysite nanotubes and stir and mix evenly to obtain component B;

[0076] S3. Load component A and component B with a volume ratio of 1:1 into two barrels of the spraying equipment respectively, and set the spraying pressure of the spraying equipment to 14MPa, the temperature to 75°C, the output to not less than 1.6kg / min, and keep the nozzle 40cm away from the surface to be sprayed during spraying.

[0077] The specific steps of the preparation method of modified halloysite nanotubes in S2 are:

[0078] S2-1, surface treatment: 3g of halloysite nanotubes were dispersed and soaked in 300ml of 0.1mol dilute hydrochloric acid solution, and ultrasonicated at 20-50kHz for 40min at 20-25°C, and then stirred at room temperature for 4h to obtain a suspension, and then the suspension was separated, and the separated nanotubes were washed with deionized water until neutral, and then dried in a vacuum drying oven at 80°C for 12h;

[0079] S2-2, modification treatment: grind the surface-treated halloysite nanotubes into powder with a particle size of 50-100 nm, add them into 100 ml of silane coupling agent solution with a concentration of 3.5 vol.%, and perform ultrasonic dispersion at a temperature of 25° C. and a frequency of 20-50 kHz for 60 min; wherein the silane coupling agent of the silane coupling agent solution is kH550, and the solvent is anhydrous ethanol;

[0080] S2-3. Post-treatment: heating and stirring in a water bath at 80° C. for 3 h to obtain a suspension, washing with water, washing with alcohol, and centrifuging, and drying in a vacuum drying oven at 80° C. for 12 h to obtain modified halloysite nanotubes.

[0081] Example 3

[0082] In this embodiment, a highly wear-resistant coating that can be quickly formed for industrial conveyor belts includes component A and component B. Component A is composed of diisocyanate and polyether polyol, and the free isocyanate content in component A is 17% by weight; component B is composed of 45% to 60% of amino-terminated polyether, 35% to 50% of chain extender, 1% to 3% of wear-resistant filler and 1% to 5% of additives by weight; wherein the wear-resistant filler is modified halloysite nanotubes.

[0083] The method for preparing the high wear-resistant coating for the industrial conveyor belt in this embodiment includes the following steps:

[0084] S1. Preparation of component A: 319 g of MDI-50 and 250 g of PPG-2000 were added to a glass reactor, and the mixture was kept warm in a water bath at 60° C. under a nitrogen atmosphere and stirred for 4 h to obtain a semi-prepolymer component A having a free isocyanate content of 17%;

[0085] S2. Prepare component B: according to the isocyanate index of component A and component B of 1.05, add 32 g of T5000, 368 g of D2000, 128 g of E100 and 118 g of MDBA into a beaker, stir magnetically at 70° C. until mixed evenly, and finally add 2.3 g of modified halloysite nanotubes and stir and mix evenly to obtain component B;

[0086] S3. Load component A and component B with a volume ratio of 1:1 into two barrels of the spraying equipment respectively, set the spraying pressure of the spraying equipment to 13MPa, the temperature to 70°C, the output to not less than 1.6kg / min, and keep the nozzle 45cm away from the surface to be sprayed during spraying.

[0087] The specific steps of the preparation method of modified halloysite nanotubes in S2 are:

[0088] S1. Surface treatment: 3 g of halloysite nanotubes were dispersed and soaked in 300 ml of 0.1 mol dilute hydrochloric acid solution, and ultrasonicated at 20-50 kHz for 30 min at 20-25 °C, and then stirred at room temperature for 2 h to obtain a suspension, and then the suspension was separated, and the separated nanotubes were washed with deionized water until neutral, and then dried in a vacuum drying oven at 60 °C for 12 h;

[0089] S2, modification treatment: grinding the surface-treated halloysite nanotubes into powder with a particle size of 50-100 nm, adding them into 100 ml of a silane coupling agent solution with a concentration of 3.5 vol.%, and performing ultrasonic dispersion at a temperature of 25° C. and a frequency of 20-50 kHz for 60 min; wherein the silane coupling agent of the silane coupling agent solution is kH550, and the solvent is anhydrous ethanol;

[0090] S3. Post-treatment: heating and stirring in a water bath at 70° C. for 3 h to obtain a suspension, washing with water, washing with alcohol, and centrifuging, and drying in a vacuum drying oven at 70° C. for 12 h to obtain modified halloysite nanotubes.

[0091] Example 4

[0092] In this embodiment, the highly wear-resistant coating that can be quickly formed for industrial conveyor belts includes component A and component B. Component A is composed of diisocyanate and polyether polyol, and the free isocyanate content in component A is 19% by weight; component B is composed of 45% to 60% of amino-terminated polyether, 35% to 50% of chain extender, 1% to 3% of wear-resistant filler and 1% to 5% of additives by weight; wherein the wear-resistant filler is modified halloysite nanotubes.

[0093] The method for preparing the high wear-resistant coating for the industrial conveyor belt in this embodiment includes the following steps:

[0094] S1. Preparation of component A: 368 g of MDI-50 and 250 g of PPG-2000 were added to a glass reactor, and the mixture was kept warm in a water bath at 70° C. under a nitrogen atmosphere and stirred for 4 h to obtain component A having a free isocyanate content of 19%;

[0095] S2. Prepare component B: according to the isocyanate index of component A and component B of 1.05, add 32 g of T5000, 373 g of D2000, 130 g of E100 and 120 g of MDBA into a beaker, stir magnetically at 70° C. until mixed evenly, and finally add 3.0 g of modified halloysite nanotubes and stir and mix evenly to obtain component B;

[0096] S3. Load component A and component B with a volume ratio of 1:1 into two barrels of the spraying equipment respectively, and set the spraying pressure of the spraying equipment to 12MPa, the temperature to 75°C, and the output to be not less than 1.6kg / min. During spraying, keep the nozzle 50cm away from the surface to be sprayed.

[0097] The specific steps of the preparation method of modified halloysite nanotubes in S2 are:

[0098] S1. Surface treatment: 3 g of halloysite nanotubes were dispersed and soaked in 300 ml of 0.1 mol dilute hydrochloric acid solution, and ultrasonicated at 20-50 kHz for 35 min at 20-25 °C, and then stirred at room temperature for 3 h to obtain a suspension, and then the suspension was separated, and the separated nanotubes were washed with deionized water until neutral, and then dried in a vacuum drying oven at 70 °C for 12 h;

[0099] S2, modification treatment: grinding the surface-treated halloysite nanotubes into powder with a particle size of 50-100 nm, adding them into 100 ml of a silane coupling agent solution with a concentration of 3.5 vol.%, and performing ultrasonic dispersion at a temperature of 25° C. and a frequency of 20-50 kHz for 60 min; wherein the silane coupling agent of the silane coupling agent solution is kH550, and the solvent is anhydrous ethanol;

[0100] S3. Post-treatment: heating and stirring in a water bath at 70° C. for 4 h to obtain a suspension, washing with water, washing with alcohol, and centrifuging, and drying in a vacuum drying oven at 70° C. for 24 h to obtain modified halloysite nanotubes.

[0101] Example 5

[0102] In this embodiment, the highly wear-resistant coating that can be quickly formed for industrial conveyor belts includes component A and component B. Component A is composed of diisocyanate and polyether polyol, and the free isocyanate content in component A is 18.2% by weight; component B is composed of 45% to 60% of amino-terminated polyether, 35% to 50% of chain extender, 1% to 3% of wear-resistant filler and 1% to 5% of additives by weight; wherein the wear-resistant filler is modified halloysite nanotubes.

[0103] The method for preparing the high wear-resistant coating for the industrial conveyor belt in this embodiment includes the following steps:

[0104] S1. Preparation of component A: 364 g of MDI-50 and 250 g of PPG-2000 were added to a glass reactor, and the mixture was kept warm in a water bath at 60° C. under a nitrogen atmosphere and stirred for 4 h to obtain component A having a free isocyanate content of 18.2%;

[0105] S2. Prepare component B: according to the isocyanate index of component A and component B of 1.1, add 30 g of T5000, 373 g of D2000, 105 g of E100 and 100 g of MDBA into a beaker, stir magnetically at 70° C. until mixed evenly, and finally add 2.3 g of modified halloysite nanotubes and stir and mix evenly to obtain component B;

[0106] S3. Load component A and component B with a volume ratio of 1:1 into two barrels of the spraying equipment respectively, and set the spraying pressure of the spraying equipment to 13MPa, the temperature to 75°C, the output to not less than 1.6kg / min, and keep the nozzle 45cm away from the surface to be sprayed during spraying.

[0107] The specific steps of the preparation method of modified halloysite nanotubes in S2 are:

[0108] S1. Surface treatment: 3 g of halloysite nanotubes were dispersed and immersed in 300 ml of 0.1 mol dilute hydrochloric acid solution, and ultrasonicated at 20-50 kHz for 35 min at 20-25 °C, and then stirred at room temperature for 1 h to obtain a suspension, and then the suspension was separated, and the separated nanotubes were washed with deionized water until neutral, and then dried in a vacuum drying oven at 60 °C for 12 h;

[0109] S2, modification treatment: grinding the surface-treated halloysite nanotubes into powder with a particle size of 50-100 nm, adding them into 100 ml of a silane coupling agent solution with a concentration of 3.5 vol.%, and performing ultrasonic dispersion at a temperature of 25° C. and a frequency of 20-50 kHz for 60 min; wherein the silane coupling agent of the silane coupling agent solution is kH550, and the solvent is anhydrous ethanol;

[0110] S3. Post-treatment: heating and stirring in a water bath at 65° C. for 3 h to obtain a suspension, washing with water, washing with alcohol, and centrifuging, and drying in a vacuum drying oven at 50° C. for 12 h to obtain modified halloysite nanotubes.

[0111] Example 6

[0112] In this embodiment, a highly wear-resistant coating that can be quickly formed for industrial conveyor belts includes component A and component B. Component A is composed of diisocyanate and polyether polyol, and the free isocyanate content in component A is 17% by weight; component B is composed of 45% to 60% of amino-terminated polyether, 35% to 50% of chain extender, 1% to 3% of wear-resistant filler and 1% to 5% of additives by weight; wherein the wear-resistant filler is modified halloysite nanotubes.

[0113] The method for preparing the high wear-resistant coating for the industrial conveyor belt in this embodiment includes the following steps:

[0114] S1. Preparation of component A: 319 g of MDI-50 and 250 g of PPG-2000 were added to a glass reactor, and the mixture was kept warm in a water bath at 60° C. under a nitrogen atmosphere and stirred for 4 h to obtain component A having a free isocyanate content of 17%;

[0115] S2. Prepare component B: according to the isocyanate index of component A and component B of 1.1, add 32 g of T5000, 373 g of D2000, 128 g of E100 and 120 g of MDBA into a beaker, stir magnetically at 70° C. until mixed evenly, and finally add 2.0 g of modified halloysite nanotubes and stir and mix evenly to obtain component B;

[0116] S3. Load component A and component B with a volume ratio of 1:1 into the barrel of the spray equipment respectively, set the spraying pressure of the spray equipment to 13MPa, the temperature to 70°C, the output to be not less than 1.6kg / min, and keep the nozzle 50cm away from the surface to be sprayed during spraying.

[0117] The specific steps of the preparation method of modified halloysite nanotubes in S2 are:

[0118] S1. Surface treatment: 3 g of halloysite nanotubes were dispersed and soaked in 300 ml of 0.1 mol dilute hydrochloric acid solution, and ultrasonicated at 20-50 kHz for 30 min at 20-25 °C, and then stirred at room temperature for 2 h to obtain a suspension, and then the suspension was separated, and the separated nanotubes were washed with deionized water until neutral, and then dried in a vacuum drying oven at 60 °C for 12 h;

[0119] S2, modification treatment: grinding the surface-treated halloysite nanotubes into powder with a particle size of 50-100 nm, adding them into 100 ml of a silane coupling agent solution with a concentration of 3.5 vol.%, and performing ultrasonic dispersion at a temperature of 25° C. and a frequency of 20-50 kHz for 60 min; wherein the silane coupling agent of the silane coupling agent solution is kH550, and the solvent is anhydrous ethanol;

[0120] S3. Post-treatment: heating and stirring in a water bath at 70° C. for 3 h to obtain a suspension, washing with water, washing with alcohol, and centrifuging, and drying in a vacuum drying oven at 80° C. for 12 h to obtain modified halloysite nanotubes.

[0121] After the wear-resistant coating is cured and cured at room temperature for seven days away from light, testing can be carried out.

[0122] The wear resistance test method for the high wear-resistant coating that can be quickly formed for industrial conveyor belts of the present invention is as follows:

[0123] The wear resistance of the coating was tested using a Taber wear tester. The grinding wheel used was an H-18 grinding wheel with a weight of 750g and a grinding wheel speed of 60r / min. The weight loss was determined by measuring the difference in coating weight before and after the experiment after every 500 rounds of friction. The smaller the weight loss, the better the wear resistance.

[0124] Table 1 compares the wear resistance and curing time of the high wear-resistant coating for industrial conveyor belts prepared in Examples 1 to 6 and epoxy-polyamide, epoxy-phenolic, epoxy-modified silicone, natural rubber, and nitrile rubber coatings.

[0125] Table 1

[0126]

[0127]

[0128] It can be seen from the data in Table 1 that the wear-resistant coating prepared by the present invention has a smaller weight loss and better wear resistance than the currently commonly used polymer wear-resistant coating, and the coating has a short curing time, so the coating of the industrial conveyor belt can be completed quickly, meeting the wear resistance requirements and realizing application.

[0129] Figure 1 The wear-resistant coatings prepared in Examples 1 to 6 and the blank control are subjected to changes in the impact force when a falling ball falls from a height of 100 cm in an impact test.

[0130] The impact test uses a falling ball impact test to test the impact resistance of the sample. The principle of the test is to drop a sphere of known mass freely from a certain height to make it collide with the material being tested. By measuring the energy loss of the sphere during the collision, the impact resistance of the material or structure being tested can be evaluated. Figure 1 As shown in , the impact force in all embodiments increases rapidly to a peak value over time, and then decreases rapidly, while the coating does not break macroscopically. This shows that after the sphere hits the coating, the impact force is quickly absorbed and released. The peak impact force of Examples 1 to 6 is lower than that of the blank control, that is, the small ball acts directly on the sensor in free fall, which shows that the coatings of Examples 1 to 6 all show certain impact resistance, which can reduce the impact force of the sphere when it falls and play a certain degree of buffering and shock absorbing effect. In the actual production process, the rapid prototyping of high-wear-resistant coatings can effectively reduce the impact from complex conditions such as falling rocks, extend the service life of the conveyor belt, and thus improve production efficiency.

[0131] Table 2 is a comparison of the mechanical properties of the wear-resistant coatings sprayed with the present invention obtained in Examples 1 to 6.

[0132] Table 2

[0133]

[0134] From the data in Table 2, it can be seen that after the A and B components of the high wear-resistant coating for industrial conveyor belts prepared by the present invention are adjusted, the tensile strength of the prepared wear-resistant coating can reach up to 20.92MPa, the elongation at break is as high as 654%, and the impact toughness reaches 60MJ / m 3 , compared with the existing wear-resistant coatings used in industrial conveyor belts, it has better mechanical properties.

[0135] like Figure 2 As shown in the figure, the 6 curves respectively represent the stress changes of the wear-resistant coatings prepared in Examples 1 to 6 under different strains, which complement the data in the above Table 2, and more intuitively show that within the composition ratio range that conforms to the scheme of the present application, a high wear-resistant coating with higher strength and toughness that can be quickly formed can be produced.

Claims

1. Rapidly prototypable high wear-resistant coating for industrial conveyor belts, characterized in that: The invention comprises a component A and a component B, wherein the component A is composed of diisocyanate and polyether polyol, and the free isocyanate content in the component A is 13% to 21% by weight. In terms of weight percentage, the B component is composed of 45% to 60% of amino-terminated polyether, 35% to 50% of chain extender, 1% to 3% of wear-resistant filler and 1% to 5% of auxiliary agent; The isocyanate index of the A component and the B component is 1.05 to 1.

1.

2. The high wear-resistant coating for industrial conveyor belts capable of rapid prototyping according to claim 1, characterized in that: In terms of weight percentage, the diisocyanate in the component A accounts for 45% to 70%, and the polyether polyol accounts for 30% to 55%.

3. The high wear-resistant coating for industrial conveyor belts capable of rapid prototyping according to claim 1, characterized in that: The diisocyanate is any one or more of MDI, IPDI and TDI in any proportion.

4. The high wear-resistant coating for industrial conveyor belts capable of rapid prototyping according to claim 1, characterized in that: The polyether polyol is any one of PPG2000 and PTMG1000 or two of them in any proportion.

5. The high wear-resistant coating for industrial conveyor belts capable of rapid prototyping according to claim 1, characterized in that: The amino-terminated polyether is any one or more of D400, D2000 and T5000 in any proportion.

6. The high wear-resistant coating capable of rapid prototyping for industrial conveyor belts according to claim 1, characterized in that: The chain extender is any one or more of E100, E230, W6200, propylene glycol diethyl ester (PGDA), 4,4'-di-sec-butylaminodiphenylmethane (MDBA), BYK-P-104, BYK-104S, dibutyl phthalate (DBP), dioctyl phthalate (DOP), propyl carbonate (PC), and ethyl carbonate (EC) in any proportion.

7. The high wear-resistant coating capable of rapid prototyping for industrial conveyor belts according to claim 1, characterized in that: The auxiliary agent is any one or more of dibutyl phthalate (DBP), dioctyl phthalate (DOP), propyl carbonate (PC), ethyl carbonate (EC), -P-104, BYK-104S, and dimethyl methylphosphonate (DMMP) in any proportion.

8. The high wear-resistant coating capable of rapid prototyping for industrial conveyor belts according to claim 1, characterized in that: The wear-resistant filler is modified halloysite nanotube.

9. The method for preparing a high wear-resistant coating capable of rapid prototyping for an industrial conveyor belt according to any one of claims 1 to 8, characterized in that: Follow the steps below to implement it: S1. Preparation of component A: diisocyanate was added to a glass reactor, and polyether polyol was slowly added through a constant pressure dropping funnel under a nitrogen atmosphere until the free isocyanate content was 13% to 21%, and then heated to 50 to 80° C., kept warm and stirred for 2 to 6 hours to obtain component A; S2. Preparation of component B: According to the isocyanate index of component A and component B of 1.05 to 1.1, determine the weight percentage of each component in component B, first take the amino-terminated polyether, chain extender and auxiliary agent and stir and mix them evenly in the temperature range of 50 to 80° C., then add the wear-resistant filler and continue stirring for 1 to 3 hours until fully mixed to obtain component B; S3, respectively loading component A and component B with a volume ratio of 1:1 into the barrel of the spraying equipment; The spraying pressure of the spraying equipment is set to 12-14 MPa, the temperature is 70-75°C, and the output is not less than 1.6 kg / min; the nozzle is kept at a distance of 35-50 cm from the surface to be sprayed for spraying.

10. The method for preparing a high wear-resistant coating capable of rapid prototyping for an industrial conveyor belt according to claim 9, characterized in that: The wear-resistant filler in S2 is a modified halloysite nanotube, and the preparation method of the modified halloysite nanotube is specifically implemented according to the following steps: S2-1, surface treatment: halloysite nanotubes (HNTs) are dispersed and immersed in a dilute hydrochloric acid solution with a pH value of 2 to 3, and ultrasonically treated at a temperature of 20 to 25°C with a frequency of 20 to 50 kHz for 20 to 40 minutes, and then stirred at room temperature for 1 to 4 hours to obtain a suspension, and then the suspension is separated, and the separated nanotubes are washed with deionized water until neutral, and then dried in a vacuum drying oven at 50 to 80°C for 12 to 24 hours; S2-2, modification treatment: grinding the surface-treated halloysite nanotubes into powder with a particle size of 50 to 100 nm, adding the powder to a silane coupling agent solution, and performing ultrasonic dispersion at a temperature of 20 to 25° C. and a frequency of 20 to 50 kHz for 30 to 60 minutes; The concentration of the silane coupling agent solution is 2-4 vol.%, the silane coupling agent is kH550 or kH570, and the solvent is anhydrous ethanol; S2-3, post-treatment: heating in a water bath at 50-70°C with stirring for 2-4 hours to obtain a suspension; washing with water, washing with alcohol, centrifuging, and drying in a vacuum drying oven at 50-80°C for 12-24 hours to obtain completely dried modified halloysite nanotubes.

Citation Information

Patent Citations

  • A superhydrophobic and superoleophobic antireflective glass surface layer and its preparation method

    CN103951278B

  • Titanium carbide wear-resistant ceramic coating, its preparation method and application

    CN110318036B

  • Spray polyurea elastomer for mine, preparation and construction method thereof

    CN101302393A

  • Surface modification treatment method of halloysite nanotube

    CN104119704A

  • Underwater anti-impact coating with rapid curing function

    CN107523205A